COLCHICINE POISONING - A REVIEW OF MEDICOLEGAL ASPECTS (Journal of Forensic Medicine & Toxicology, 2014)
Medicolegal experts frequently come across poisonings resulting from intentional or unintentional exposure to toxic plants and their products. In this regard, colchicine poisoning is infrequently reported in the region and thus needs an elaboration. This article focuses on the autopsy observations and other medicolegal aspects of colchicine poisoning which assumes significance, especially because of its narrow therapeutic index as a drug, mistaken identity and consumption of the plant, its high toxicity and fatal outcome due to multi-organ failure.
Keywords: Colchicine; Poisoning; Autopsy; Histopathology; Toxicological analysis; Medicolegal aspects